Faktor-Faktor Yang Mempengaruhi Efektivitas Pembiayaan Mikro Syariah - Murniati, Murniati; Nia, Murni; Nurjana, Nurjana; Muh. Syata, Wahyu (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to determine the factors influencing the effectiveness of Islamic microfinance in increasing small business revenues in Kendari. This research uses a quantitative descriptive approach with a survey approach. The study will be conducted in Kendari City, Southeast Sulawesi, specifically in Wowawanggu Village, Kadia District. The sample size for this study is 20 respondents. Data collection techniques will include questionnaires, observation, interviews, and documentation. Data analysis techniques will include regression and descriptive analysis. The results indicate that factors supporting the effectiveness of Islamic microfinance in Kendari include fair and transparent contracts in accordance with Islamic principles, relatively easy disbursement procedures and monitoring by financial institutions, as well as education, financial guidance, and a sense of security in transactions. Furthermore, factors inhibiting the effectiveness of Islamic microfinance in Kendari include low levels of Islamic financial literacy among the public, initial administration perceived as complicated by some business actors, and less than optimal business locations, resulting in less than optimal results. Therefore, collaboration between financial institutions, the government, and business actors is needed to overcome these obstacles and optimize the benefits of Islamic microfinance